Morphology, Diet and Flower‐visiting by Phyllostomid Bats in Cuba. (10th June 2014) - Clairmont, Lindsey; Mora, Emanuel C.; Fenton, Brock
Abstract Pollinator morphology can play an important role in structuring plant–pollinator relationships and a pollinator's morphology may be associated with aspects of its diet. We examined the relationship between morphology and the partitioning of flower‐based food resources for five species of flower‐visiting Cuban bats: Artibeus jamaicensis, Brachyphylla nana, Erophylla sezekorni, Monophyllus redmani and Phyllonycteris poeyi. We analyzed cranial traits and body size to assess differences among species with respect to morphological specializations. We also collected dietary data from guano and used acoustic monitoring to assess bat activity at flowers. We found evidence that bats partition floral resources, but we found no direct evidence that plants were limiting resources for the bats. Morphological similarity among bat species did not predict dietary overlap. Rather it was associated with phylogenic relationships among some species. Species with different morphological specialization for flower‐visiting consumed resources and visited food plants at different frequencies.